Food-Based Dietary Guidelines for the Arab Gulf Countries - Abdulrahman O. Musaiger; Hamed R. Takruri; Abdelmonem S. Hassan; Hamza Abu-Tarboush (Journal of Nutrition and Metabolism)
The concept of food-based dietary guidelines (FBDG) has been promoted by several international organizations. However, there are no FBDG for the countries in the Arab region. As the Arab Gulf countries share similar a socioeconomic and nutrition situation, an attempt was made to develop FBDG for these countries. This paper summarizes the steps taken to develope such guidelines by the Arab Center for Nutrition. The FBDG were developed through 6 steps: (1) determination of the purpose and goals for establishing FBDG, (2) characteristics of FBDG, (3) determination of the food consumption patterns, (4) review the current nutrition situation, (5) determination of the lifestyle patterns that are associated with diet-related diseases and (6) formulating the FBDG. The FBDG consist of 14 simple and practical pieces of advice taking into consideration the sociocultural status and nutritional problems in the Arab Gulf countries. The FBDG can be a useful tool in educating the public in healthy eating and prevention of diet-related chronic diseases.